Preferential antitumor effect of the Src inhibitor dasatinib associated with a decreased proportion of aldehyde dehydrogenase 1-positive cells in breast cancer cells of the basal B subtype - Kurebayashi, Junichi (BioMed Central, 2010)
BACKGROUND: Recent studies have suggested that the Src inhibitor dasatinib preferentially inhibits the growth of breast cancer cells of the basal-like subtype. To clarify this finding and further investigate combined antitumor effects of dasatinib with cytotoxic agents, a panel of breast cancer cell lines of various subtypes was treated with dasatinib and/or chemotherapeutic agents. METHODS: Seven human breast cancer cell lines were treated with dasatinib and/or seven chemotherapeutic agents. Effects of the treatments on c-Src activation, cell growth, cell cycle, apoptosis and the proportion of aldehyde dehydrogenase (ALDH) 1-positive cells were examined. RESULTS: The 50%-growth inhibitory concentrations (IC(50)s) of dasatinib were much lower in two basal B cell lines than those in the other cell lines. The IC(50)s of chemotherapeutic agents were not substantially different among the cell lines. Dasatinib enhanced antitumor activity of etoposide in the basal B cell lines. Dasatinib induced a G1-S blockade with a slight apoptosis, and a combined treatment of dasatinib with etoposide also induced a G1-S blockade in the basal B cell lines. Dasatinib decreased the expression levels of phosphorylated Src in all cell lines. Interestingly, dasatinib significantly decreased the proportion of ALDH1-positive cells in the basal B cell lines but not in the other cell lines. CONCLUSIONS: The present study indicates that dasatinib preferentially inhibits the growth of breast cancer cells of the basal B subtype associated with a significant loss of putative cancer stem cell population. A combined use of dasatinib with etoposide additively inhibits their growth. Further studies targeting breast cancers of the basal B subtype using dasatinib with cytotoxic agents are warranted.